Damsgård. En overpløjet høj fra ældre bronzealder per. III med stenkiste og ligbrændingsgrube - Olsen, Anne-Louise Haack; Bech, Jens-Henrik; Bennike, Pia; Christensen, Kjeld; Robinson, David Earle; Andersen, Svend Th.; Robinson, David Earle (Kuml, 1994)